The Last Kiss - L'ultimo bacio - Gabriele Muccino (2001)
Carlo is a twenty-nine-year-old man who works in an advertisement agency and has been living with his girlfriend Giulia for three years. When she gets pregnant and he meets the stunning eighteen-year-old Francesca, his relationship with Giulia moves into a crisis, since he is not ready to reach adulthood. Francesca has a crush on Carlo and dreams of him. His three best friends also have problems with their mates: Adriano has just had a son and has problems with taking the responsibilities of fatherhood, while his wife Livia becomes very connected to the baby, neglecting their marriage; Alberto has no ties with any woman, limiting to use them sexually; and Paolo has a passion for his former lover. Meanwhile, Giulia's mother Anna has a middle-age crisis, jeopardizing her marriage.
Keywords: Comedy, Drama, Romance